A critical review on TiO2 based photocatalytic CO2 reduction system: Strategies to improve efficiency. (July 2018) - Shehzad, Nasir; Tahir, Muhammad; Johari, Khairiraihanna; Murugesan, Thanabalan; Hussain, Murid
Graphical abstract: Highlights: Strategies to improve efficiency of photocatalytic CO2 reduction. Thermodynamic, mass transfer and selectivity of solar product. Visible light response, charge separation and CO2 adsorption of TiO2 . Surface plasmon resonance effect of metals and graphene. Graphene modified TiO2 nanocomposites. Abstract: The massive burning of fossil fuels to fulfill the augmenting energy demands of world have triggered the ever-increasing emission of carbon dioxide (CO2 ); the main cause of global warming. Photocatalytic reduction of CO2 into solar fuels and chemicals using everlasting solar energy seems promising technology to contemporaneously curb the globa1 warming and partially fulfill the energy requirements. This study focused on understanding the main challenges in photocatalytic CO2 reduction systems and strategies to improve the efficiency of solar fuels production. The overview of fundamentals and latest developments in titania (TiO2 ) based photocatalytic CO2 reduction systems have been discussed. More specifically, thermodynamics, mass transfer, selectivity and reaction mechanism of photocatalytic CO2 reduction are critically deliberated. In the main stream, developments have been categorized as strategies to enhance the different aspects such as visible light response, charge separation, CO2 adsorption and morphology of photo-catalysts for TiO2 based photocatalytic CO2 reduction systems. Different modification techniques to overcome the low efficiency by fabricating advance TiO2 nanocomposites through surface modifications, doping of metals, non-metals and semiconductor are discussed. The challenges lingering on against achieving the higher photocatalytic conversion of CO2 into solar fuels are also investigated. In conclusion, brief perspectives and recommendations on the development of efficient photocatalysts are outlined which would be of vital importance for the improvements of conversion efficiency of CO2 reduction system.